Relación entre la aparición de los pliegues conjuntivales paralelos al parpado (LIPCOF) y epiteliopatía del parpado en efecto parabrisas (LWE) asociados al uso de LC (2020)
The appearance of conjunctival folds parallel to the eyelid (LIPCOF) and epitheliopathy of the eyelid in effect windshield (LWE) are caused by the friction that occurred during blinking, due to the instability of the tear film that being in presence with another surface as a contact lens will occur more quickly, because it will also depend on the characteristics of the same.